2022
DOI: 10.18240/ijo.2022.07.09
|View full text |Cite
|
Sign up to set email alerts
|

Neuromyelitis optica spectrum disorders and anti-myelin oligodendrocyte glycoprotein positive optic neuropathies

Abstract: AIM: To describe the clinical characteristics and treatments associated with antibody positive optic neuropathies including anti-myelin oligodendrocyte glycoprotein (MOG) and anti-aquaporin 4 (AQP4), alongside diagnostic modalities, investigations, and outcomes. METHODS: A cross-sectional single-centre retrospective case series consisting of 16 patients including 12 anti-MOG positive patients and 4 anti-AQP4 positive patients. Each of these patients had clinical signs and symptoms of optic neuritis and consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Each of these classical features of NAION 9 , 18 , 24 can be found in around 10%–30% of patients with MOGAD-ON. 9 , 25 However, when considered together with optic disc edema, only 1 (1.6%) patient with MOGAD-ON in our cohort had all of these 3 NAION predictors combined. If eye pain was included as a differentiator, these combined features had 100% specificity in differentiating MOGAD-ON from NAION.…”
Section: Discussionmentioning
confidence: 69%
“…Each of these classical features of NAION 9 , 18 , 24 can be found in around 10%–30% of patients with MOGAD-ON. 9 , 25 However, when considered together with optic disc edema, only 1 (1.6%) patient with MOGAD-ON in our cohort had all of these 3 NAION predictors combined. If eye pain was included as a differentiator, these combined features had 100% specificity in differentiating MOGAD-ON from NAION.…”
Section: Discussionmentioning
confidence: 69%
“…In comparative studies, this proportion has been shown to be greater than in AQP4-ON (28-50%) and seronegative ON, including MS (10-46%) [48,51,58]. The majority of eye pain in MOG-ON is pain related to eye movement, with periocular pain being less common [56,57]. Pain on eye movement may arise from traction on the common tendinous ring caused by retro-orbital pathology, whereas periocular pain is presumed to be governed by the trigeminal nerve.…”
Section: Eye Painmentioning
confidence: 97%
“…Eye pain may be common in MOG-ON, reported in 73-92% of cases internationally [42,43,48,51,56,57]. In comparative studies, this proportion has been shown to be greater than in AQP4-ON (28-50%) and seronegative ON, including MS (10-46%) [48,51,58].…”
Section: Eye Painmentioning
confidence: 98%
See 2 more Smart Citations